Storage of TamarilloiIn Active Packaging Using Oxygen, Carbondioxide, Moisture, and Ethylene Scavengers - Joncer Naibaho; Elisa Julianti; Era Yusraini (Universitas Sumatera Utara, 2013)
Utilization of modified atmosphere packaging actively or passively can extend the shelf life of fruits. Research has been carried out using completely randomized factorial design with two factors. The first factor was the method of packaging namely active packaging with oxygen scavenger, oxygen and carbondioxide scavengers, oxygen and water vapor scavengers, ethylene scavenger, oxygen, carbon dioxide, water vapor and ethylene scavengers, passive packaging, and no packaging as a control. The second factor was storage time namely stored 1, 2, 3, and 4 weeks. Parameters measured were carbondioxide levels, moisture content, weight reduction, vitamin C content, hardness, total soluble solid, total acid content, color scores and organoleptic of color, flavour and texture. The results showed that the method of packaging had a highly significant effect on all parameters except vitamin C content. Storage time had affected all parameters. Treatment interaction had highly significant effect on moisture content, weight reduction, hardness, total soluble solid, and total acid. Tamarillo fruits packed in active modified atmosphere packaging with oxygen and moisture scavengers (P3) was the best treatment as compared to other types of modified atmosphere packaging for 4 weeks of storage. Keywords: Tamarillo, Active Packaging, Scavenger, Storage